Exploring Amyloidogenicity of Peptides From Ribosomal S1 Protein to Develop Novel AMPs - Galzitskaya, Oxana V. (Frontiers in Molecular Biosciences, 2021)
Antimicrobial peptides (AMPs) and similar compounds are potential candidates for combating antibiotic-resistant bacteria. The hypothesis of directed coaggregation of the target protein and an amyloidogenic peptide acting as an antimicrobial peptide was successfully tested for peptides synthesized on the basis of ribosomal S1 protein in the bacterial culture of T. thermophilus. Coaggregation of the target protein and amyloidogenic peptide was also tested for the pathogenic ribosomal S1 protein from P. auregenosa. Almost all peptides that we selected as AMPs, prone to aggregation and formation of fibrils, based on the amino acid sequence of ribosomal S1 protein, formed amyloid fibrils. We have demonstrated that amyloidogenic peptides are not only toxic to their target cells, but also some of them have antimicrobial activity. Controlling the aggregation of vital bacterial proteins can become one of the new directions of research and form the basis for the search and development of targeted antibacterial drugs.